Acute Stress and Gender Effects in Sensory Gating of the Auditory Evoked Potential in Healthy Subjects - Zengyou Xin; Simeng Gu; Wei Wang; Yi Lei; Hong Li (Neural Plasticity)
Sensory gating is a neurophysiological measure of inhibition that is characterized by a reduction in the P50, N100, and P200 event-related potentials to a repeated identical stimulus. It was proposed that abnormal sensory gating is involved in the neural pathological basis of some severe mental disorders. Since then, the prevailing application of sensory gating measures has been in the study of neuropathology associated with schizophrenia and so on. However, sensory gating is not only trait-like but can be also state-like, and measures of sensory gating seemed to be affected by several factors in healthy subjects. The objective of this work was to clarify the roles of acute stress and gender in sensory gating. Data showed acute stress impaired inhibition of P50 to the second click in the paired-click paradigm without effects on sensory registration leading to worse P50 sensory gating and disrupted attention allocation reflected by attenuated P200 responses than control condition, without gender effects. As for N100 and P200 gating, women showed slightly better than men without effects of acute stress. Data also showed slightly larger N100 amplitudes across clicks and significant larger P200 amplitude to the first click for women, suggesting that women might be more alert than men.